AN ANALYSIS OF PACHO FLORES DAILY PRATICE: WARM-UP AND TECHNICAL STUDIES FOR TRUMPET - Gabriel, Flavio (2019)
The present article presents some concepts utilized by Pacho Flores during his daily pratice on the trumpet, relate them to the tradicional methods and compare them to the pratice realized by brazilian trumpet players. Besides recording and transcribing the exercises presented by Pacho Flores at the 5º SESC International Music Festival, an online research was made with a group of a professionals and students brazilian trumpet players about their own daily pratices. The conclusions point to the possible benefits that a trumpet player could obtain while keeping a daily pratice alike Pacho Flores’ and besides that, motivated the elaboration of an autoral method in order to promote the ideas of this renowed trumpet player.